PENGARUH UKURAN PERUSAHAAN, KINERJA LINGKUNGAN DAN BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN (Studi Kasus Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Mauhibah, Ratu Habibah; Anna, Yane Devi (Accounting Undergraduate (S1) and Diploma Study Program (D3), STIE EKUITAS, 2024)
This research aims to determine the influence of company size, environmental performance and environmental costs on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. This research method uses quantitative research methods with a descriptive and verification approach. The data used in this research is secondary data in the form of financial reports and company PROPER reports. The data testing technique uses multiple linear regression. The research results show that company size and environmental costs have a partial effect on financial performance, environmental performance has no effect on financial performance. Company size, environmental performance, environmental costs simultaneously influence financial performance.